Congestion management techniques for disruption‐tolerant satellite networks. (23rd May 2017) - Madoery, Pablo G.; Fraire, Juan A.; Finochietto, Jorge M.
Summary: Delay and disruption‐tolerant networks are becoming an appealing solution for extending Internet boundaries toward challenged environments where end‐to‐end connectivity cannot be guaranteed. In particular, satellite networks can take advantage of a priori trajectory estimations of nodes to make efficient routing decisions. Despite this knowledge is already used in routing schemes such as contact graph routing, it might derive in congestion problems because of capacity overbooking of forthcoming connections (contacts). In this work, we initially extend contact graph routing to provide enhanced congestion mitigation capabilities by taking advantage of the local traffic information available at each node. However, since satellite networks data generation is generally managed by a mission operation center, a global view of the traffic can also be exploited to further improve the latter scheme. As a result, we present a novel strategy to avoid congestion in predictable delay‐ and disruption‐tolerant network systems by means of individual contact plans. Finally, we evaluate and compare the performance improvement of these mechanisms in a typical low Earth orbit satellite constellation. Abstract : Delay and disruption‐tolerant networks are becoming an appealing solution for extending Internet boundaries toward challenges environments. In particular, when applied to satellite networks, trajectories estimation can be used to improve routing decisions. However, congestion problems might arise because of capacity overbooking of forthcoming connections (contacts). In this work, we investigate different congestion mitigation and avoidance strategies based on local and global knowledge of the DTN topology.